Crystal structure of the N‐terminal methyltransferase‐like domain of anamorsin. Issue 6 (22nd November 2013) - Song, Gaojie; Cheng, Chongyun; Li, Yang; Shaw, Neil; Xiao, Zhi‐Cheng; Liu, Zhi‐Jie
ABSTRACT Anamorsin is a recently identified molecule that inhibits apoptosis during hematopoiesis. It contains an N‐terminal methyltransferase‐like domain and a C‐terminal Fe‐S cluster motif. Not much is known about the function of the protein. To better understand the function of anamorsin, we have solved the crystal structure of the N‐terminal domain at 1.8 Å resolution. Although the overall structure resembles a typical S‐adenosylmethionine (SAM) dependent methyltransferase fold, it lacks one α‐helix and one β‐strand. As a result, the N‐terminal domain as well as the full‐length anamorsin did not show S‐adenosyl‐l‐methionine (AdoMet) dependent methyltransferase activity. Structural comparisons with known AdoMet dependent methyltransferases reveals subtle differences in the SAM binding pocket that preclude the N‐terminal domain from binding to AdoMet. The N‐terminal methyltransferase‐like domain of anamorsin probably functions as a structural scaffold to inhibit methyl transfers by out‐competing other AdoMet dependant methyltransferases or acts as bait for protein–protein interactions.Proteins 2014; 82:1066–1071. © 2013 Wiley Periodicals, Inc.